The satisfaction of Takaful customer towards the services provided by the Takaful operators / Muhammad Ekhsan Mohamed Eusop - Mohamed Eusop, Muhammad Ekhsan (Faculty of Business and Management, 2011)
The research of the “Customer Satisfaction Towards the Service provided by Takaful Operators” was conducted. Organization cannot exist without customer. As such the customer must be the central focus of the organization. This research will determine whether the customer are satisfied with the service provided by Takaful operators. This is because nowadays there are a rapid growth of Takaful operators. In this study the researcher collects the information from primary and secondary data by interview from the Takaful staff in Takaful operators company. Researcher also makes observation from website and questionnaire from customer. Researcher used journal, article and text book as secondary data. This study will help the Takaful operators to identify their weakness in order to archive the high level of satisfaction towards the service provided by them. This study utilized questionnaire as the instrument for collecting data. Questionnaires have been distributed to 100 respondent and our respondent are from public that have Takaful policies. In conclusion the most important service provided by Takaful operators can be identifying. This is important because it will improve the productivity, service quality and maximized profit. From the analysis, researcher have identify the most factor that influence the customer satisfaction and the respondent profile.